UMP and BEM collaboration empowers engineering profession - Nor Salwana, Mohammad Idris (2021)
PEKAN, 26 October 2021 - Universiti Malaysia Pahang (UMP) signed a memorandum of understanding (MoU) with the Board of Engineers Malaysia (BEM) to assist engineering degree graduates in making bulk registration under the REA Registration of Engineers Act 1967.